2011
DOI: 10.1007/s00192-011-1603-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of posterior colporrhaphy on anorectal function

Abstract: Bowel evacuation and continence improve significantly 3-6 months following posterior colporrhaphy and are associated with parallel improvement in QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
1
3
1
Order By: Relevance
“…Currently, no literature is available that compares these two quality of life tools, making this a unique study. All the questionnaires have been validated and recommended for use as research tools to determine differences in quality of life as secondary post‐operative outcomes in urogynaecological surgeries . Our data confirm that these questionnaires are acceptable for use in the clinical setting and also as research tools.…”
Section: Discussionsupporting
confidence: 68%
“…Currently, no literature is available that compares these two quality of life tools, making this a unique study. All the questionnaires have been validated and recommended for use as research tools to determine differences in quality of life as secondary post‐operative outcomes in urogynaecological surgeries . Our data confirm that these questionnaires are acceptable for use in the clinical setting and also as research tools.…”
Section: Discussionsupporting
confidence: 68%
“…Our findings are consistent with the existing literature demonstrating that PR improves posterior compartment anatomy, and bowel symptoms, most often evacuation, constipation, straining, incomplete emptying, and fecal incontinence [9][10][11][12][13][14][15]. This is in contrast to the findings of one study that showed a worsening of bowel symptoms including splinting, digitation, and incontinence [5].…”
Section: (4)contrasting
confidence: 57%
“…Non-treated defects: In the case of a symptomatic low rectocele but all the other compartments are well-suspended, an isolated posterior colporrhaphy [ 33 , 34 ] was performed; A lateral defect of the anterior compartment not treated with the initial SCP was surgically addressed with a laparoscopic paravaginal repair [ 35 , 36 , 37 ]. …”
Section: Methodsmentioning
confidence: 99%
“…In the case of a symptomatic low rectocele but all the other compartments are well-suspended, an isolated posterior colporrhaphy [ 33 , 34 ] was performed;…”
Section: Methodsmentioning
confidence: 99%